Decoding ladybird's colours: Structural mechanisms of colour production and pigment modulation. - Marzia Carrada; Mohamed Haddad; Luis M San-Jose; Gonzague Agez; Jean-Marie Poumirol; Alexandra Magro (PLoS ONE)
This study investigates the mechanisms underlying colour production in the family Coccinellidae, focusing on two model species: Adalia bipunctata (L.) and Calvia quatuordecimguttata (L.). In this family, colours have traditionally been attributed primarily to pigments such as carotenoids and melanins. We propose an alternative perspective, considering the elytra as an integrated optical medium whose optical properties - and hence colouration - result from both its architectural design and the properties of its constituent materials, including matrix and pigments. In the present work, the elytron microstructure was precisely determined by transmission electron microscopy and the numerical replica was then injected into numerical simulations of the microstructure's interaction with light, showing that the elytron structure is able to select a range of wavelengths and then generate colour. Coupling these results with local pigment analyses and microstructural examination of elytra, we show that while pigments are central to patterning and contribute to colour, the overall colour also results from one or more physical mechanisms that may operate simultaneously. In the light of these results, we suggest that the complex and diverse colouration in the Coccinellidae can only be elucidated by considering the interplay of pigments and the optical properties of the elytron cuticle. From an evolutionary ecology point of view, elytra structure influence on colouration may provide new insights into colour signalling in this insect family.